Comparison of blood loss between intra-articular and intra-venous administration of tranexamic acid in primary total knee arthroplasty - Amin, Muhammad Suhail (SICOT J, 2020)
Objective: To compare the blood loss between intra-articular and intra-venous administration of tranexamic acid (TXA) in patients undergoing primary total knee arthroplasty. Design of study: It was a randomized controlled trial. Study duration and settings: This study was carried out at the Orthopedic Departments of Combined Military Hospital Lahore and Rawalpindi from Jan 2016 to March 2018. Methodology: Patients of both the genders were involved this study who had age in the rage of 40–80 years undergoing primary unilateral total knee arthroplasty for degenerative conditions like osteoarthritis and rheumatoid arthritis. These patients were randomly divided into two treatment groups. Patients in IA group received intra-articular tranexamic acid while those in IV group received intravenous tranexamic acid. From all the patients, a written signed consent was taken. Findings: Females were predominant with male-to-female ratio of 1:3.7. The mean age of the patients was 67.3 ± 8.2 years while the mean BMI was 30.9 ± 2.9 Kg/m(2). Majority (n = 191, 95.5%) of the patients had osteoarthritis while remaining 9 (4.5%) patients had rheumatoid arthritis. There was no statistically significant difference between intra-articular and intra-venous administration of tranexamic acid in terms of mean post-operative hemoglobin (9.93 ± 1.14 vs. 9.87 ± 1.26 g/dL; p-value = 0.724), mean post-operative hematocrit (34.8 ± 1.66 vs. 34.73 ± 1.27%; p-value = 0.594), and mean fall in hemoglobin (2.27 ± 0.34 vs. 2.25 ± 0.30 g/dL; p-value = 0.587) and hematocrit (2.34 ± 0.94 vs. 2.46 ± 0.28%; p-value = 0.216). Conclusion: Intra-articular administration of tranexamic acid was found to be as effective and safe as intra-venous administration in reducing blood loss in primary total knee arthroplasty. Due to convenience, the use of intra-articular administration of tranexamic acid after primary TKA may be considered in future practice.